Piglet mortality impacts economic loss: care, management and control - Devi, Bhanita; Verma, Harshit; Bharti, P K; Verma, Rishendra (Indian Farming, 2018)
Piglet mortality is of great economic concern to the farmers and pig producers. The mortality of piglets during pre-weaning phase accounts for more than 3/4th of the total piglet losses. Several factors like behavioral, non-infectious and infectious play role towards pig mortality. Usually, it is considered that 8-10% natural mortality may not cause a concern but when the mortality increases at a rapid rate, it may lead to huge economic loss as well as it would affect over all pig population in India. The proper and judicious management practices along with bio-security measures at pig farm may certainly be the prominent solution to curve the pig mortality.